2016
DOI: 10.1016/j.aogh.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Medication Use as an Indicator of Human Health Impact in Environmentally Stressed Areas

Abstract: We reviewed from literature the feasibility of medication use as an indicator of health outcomes in environmentally stressed areas, especially where a paucity of typical epidemiological and other risk-based data are encountered. The majority of studies reported were about medication use as an indicator of adverse respiratory effects from air pollution in developed countries. Studies to a lesser extent pointed to medication use as indicator of health outcomes associated with other environmental health stressors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In consequence, the significant increase in the use of measured OTC medication according to the thermal environment could be a useful tool for the surveillance of gastrointestinal and respiratory diseases to identify and anticipate outbreaks. () In this context, it should be mentioned that OTC medicines play an increasing role in managing symptoms associated with mild to moderate respiratory diseases due to the growing self‐care movement …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In consequence, the significant increase in the use of measured OTC medication according to the thermal environment could be a useful tool for the surveillance of gastrointestinal and respiratory diseases to identify and anticipate outbreaks. () In this context, it should be mentioned that OTC medicines play an increasing role in managing symptoms associated with mild to moderate respiratory diseases due to the growing self‐care movement …”
Section: Discussionmentioning
confidence: 99%
“…The consumption of medication, especially over‐the‐counter (OTC) drugs, may reflect a lesser degree of severity in morbidity. However, relatively few studies have used this response variable as the main variable, and most of those which have done so() used daily medical prescriptions or refundable drugs supplied to patients affiliated to the social security system/medical insurance, thereby limiting the results to severe or chronic cases within the framework of drug consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Point source pollutants are still able to affect air quality even in cities that may not be heavily industrialized (Oiamo et al, 2015). Geographic location is a key contributor to ambient exposure to pollutants likely increasing the prevalence of hypertension Hollingworth et al, 2016;Poulter et al, 2015).…”
Section: Multiple Exposuresmentioning
confidence: 99%
“…Neighbourhoods of lower socioeconomic status are also associated with poorer noise and air quality and higher exposure levels to environmental stressors . Traffic-related noise and particulate matter have also been associated with increased blood pressure Hollingworth et al, 2016). Morello-Frosch et al (2007) suggest that an area that has lower socioeconomic status is the result of poor planning because they are typically situated around urban areas that are heavily polluted because of industrialized patterns.…”
Section: Rationale and Objectivesmentioning
confidence: 99%
“…Medication use has been shown to be a more objective and reliable measure of health outcomes than health measures based on self-reported symptoms alone [14,15]. A review of the literature has indicated that when medication use is available, it should be considered a feasible (and perhaps preferable) indicator of environmental health [16]. A small number of studies have focused on the relationship between aircraft noise levels and medication use by airport residents, suggesting an association with the use of antihypertensive medication, and possibly psychotropic drugs or sleep medication [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%